2023
DOI: 10.1001/jamanetworkopen.2023.37679
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Ideation, Plans, and Attempts Among Military Veterans vs Nonveterans With Disability

Rebecca K. Blais,
Zhigang Xie,
Anne V. Kirby
et al.

Abstract: ImportancePeople with disability are at heightened risk for suicide ideation, planning, and attempt, with risk growing as the number of disabling limitations increases. Military veterans have higher rates of suicide deaths and disability relative to nonveterans.ObjectiveTo evaluate whether veteran status is associated with greater risk for suicide in those with disability.Design, Setting, and ParticipantsThis survey study used cross-sectional self-reported data from US adults who participated in the 2015-2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…More research is needed to identify more prominent risk factors for rural veterans and identify relevant protective factors among these groups. Relevant protective factors against alcohol misuse or suicide risk could include access to psychosocial support services (e.g., Straus et al, 2019), living and housing stability, employment (Elbogen et al, 2020), and disability status (Blais et al, 2023). This latter factor may be protective because of its association with support resources and greater stability associated with the support of said resources.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to identify more prominent risk factors for rural veterans and identify relevant protective factors among these groups. Relevant protective factors against alcohol misuse or suicide risk could include access to psychosocial support services (e.g., Straus et al, 2019), living and housing stability, employment (Elbogen et al, 2020), and disability status (Blais et al, 2023). This latter factor may be protective because of its association with support resources and greater stability associated with the support of said resources.…”
Section: Discussionmentioning
confidence: 99%
“…International wars, civil wars, proxy battles, conflicts, invasions, and insurgencies all end badly. They are all accompanied and followed by disruptions in the delivery of basic social services, especially access to healthcare, which has led to epidemics and spikes in infection and diseases, critical battle-related injuries, and chronic disability ( Blais et al, 2023 ), acute malnutrition, acute and chronic mental health conditions, and horrific deaths ( Sher, 2023 ). Wars always result in widespread suffering, enduring stress, trauma, loss, and population displacement, which can reverberate and scar the well-being of future generations.…”
mentioning
confidence: 99%
“…Living in war-torn countries has been associated with physical handicaps, and mental and psychological anguish (due to exposure to death). Complaints such as post-traumatic stress disorder (PTSD), anxiety, depression, sleeplessness, nightmares ( Birhan et al, 2023 ; Pavlova et al, 2023 ; Rogowska & Pavlova, 2023 ), alcohol and substance abuse ( Dissanayake et al, 2023 ), suicidal thoughts, tendencies, and attempted suicides ( Blais et al, 2023 ; Sher, 2023 ) sexual and non-sexual violence ( Hladik et al, 2023 ), and psychosomatic disorders all have been reported. These will have long-lasting effects on affected individuals.…”
mentioning
confidence: 99%